2006
DOI: 10.1007/s11373-006-9108-4
|View full text |Cite
|
Sign up to set email alerts
|

The mortality of MOP3 deficient mice with a systemic functional failure

Abstract: SummaryMOP3 (also known as BMAL1), a master regulator of circadian rhythm, plays important roles in the regulation of cell differentiation and general physical functions. In the present studies, MOP3 deficient mice had significantly reduced body weight and showed remarkable mortality around six months of age. The levels of AST, ALT, BUN, or UREA in the blood of about four month-old MOP3 )/) mice were significantly higher than MOP3 +/) or MOP3 +/+ littermates. However, no apparent pathological changes in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 11 publications
(11 reference statements)
1
25
1
Order By: Relevance
“…The Bmal1 null pups weighed significantly less than wild-type mice at weaning and failed to catch up. This finding differs slightly from previous reports (Bunger et al 2005, Sun et al 2006, where decreased BW only became evident around 20 weeks of age, secondary to progressive arthropathy interfering with normal feeding.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The Bmal1 null pups weighed significantly less than wild-type mice at weaning and failed to catch up. This finding differs slightly from previous reports (Bunger et al 2005, Sun et al 2006, where decreased BW only became evident around 20 weeks of age, secondary to progressive arthropathy interfering with normal feeding.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, as discussed above, the absence of Bmal1 gene expression may be expected to have a profound effect on reproduction. Interestingly, Bmal1 null mice have been described as 'viable and fertile' (Cowden & Simon 2002), although subsequent studies identified a spectrum of physiological changes (Kondratov et al 2006, McDearmon et al 2006, Sun et al 2006. In this report, we describe comprehensive studies on the reproductive biology of female Bmal1 null mice.…”
Section: Introductionmentioning
confidence: 89%
“…The presence of functional CRY products appears essential for tuning the ultradian GH pulsatility required for the male-specific liver activity. Similarly, previous studies reported that the circadian clock gene Bmal1 is also necessary to maintain male-female differences in body growth (33) or that liver expression of Elovl3 follows a female-like profile in male homozygous Clock/Clock mutants (19). Moreover, male rats with lesioned SCN exhibit a feminized steroid metabolism (37), as we observed for Cry Ϫ/Ϫ mice.…”
Section: Circadian Timekeeping As a Regulator Of Ultradian Ghsupporting
confidence: 85%
“…Firstly, previous studies reported that clock-deficient Bmal1 Ϫ/Ϫ or Cry Ϫ/Ϫ mice are significantly smaller than control animals (31)(32)(33). This prompted us to systematically compare the postnatal growth of Cry Ϫ/Ϫ males and females.…”
Section: Dimorphic Traits Dependent On Ultradian Gh Pulsatility Are Fmentioning
confidence: 99%
“…The functional circadian clock systems are detected in major immune cells, including macrophages (63), B cells (64,65), and natural killer cells (66 -68). It has been reported that circadian clock disruption via the shifted light/dark cycle or genetic deletion of clock genes impairs innate immunity and response to LPS treatment in mice (22,61,63).…”
Section: Serum Shock Enhances the Cry1 Protein Deubiquitination Bymentioning
confidence: 99%